ERRATUM: [Article Partial Retraction] Dyskeratosis congenita - Reports, Autopsy; Case (Autopsy and Case Reports, 2022)
Due to a desktop publishing error, the retraction notice added to article “Dyskeratosis congenita” (DOI https://doi.org/10.4322/acr.2020.203), published in Autops. Case Rep. 10 (3); 2020, was published with an error. On the retraction notice, where the text reads: Gitto L, Stoppacher R, Richardson TE, Serinelli S. Dyskeratosis congenita. Autops Case Rep [Internet]. 2021;11:e2021341. https://doi.org/10.4322/acr.2021.341 It should read: Gitto L, Stoppacher R, Richardson TE, Serinelli S. Dyskeratosis congenita. Autops Case Rep [Internet]. 2020 Jul-Sep;10(3):e2020203. https://doi.org/10.4322/acr.2020.203 The publisher apologizes for the errors.